Validity and Reliability of the Turkish Translation of the Yale Pharyngeal Residue Severity Rating Scale - ILGIN, CAN (SPRINGER, 2022)
This study aimed to assess the validity and reliability of the Turkish translation of the Yale pharyngeal residue severity rating scale. The scale measures the severity of residue in the vallecula and pyriform sinus. The original scale was translated into Turkish by two bilingual English-Turkish translators, and the Turkish version was translated back into English by two qualified professional translators to assess accuracy. The evaluators were divided into two groups (training and no-training) and two subgroups according to their experience. Intra-rater, inter-rater, and intra-class correlation coefficient measurements were analyzed by calculating agreement rates, kappa, and p values. In the analysis of the reliability, intra-class correlation coefficient values in the overall ratings for both the vallecula and the pyriform sinus were 0.9996 (95% CI 0.9992-0.9998) and 0.9997 (95% CI 0.9995-0.9999), respectively (p < 0.01). High agreement (> 95%) and perfect Fleiss kappa values were obtained for the vallecula and pyriform sinus ratings in the inter-rater initial assessments (kappa = 0.959 and kappa = 0.967, respectively). Perfect kappa values were found in the intra-rater results for both the vallecula and pyriform sinus (alpha = 0.9959 and kappa = 0.9959, respectively). In the inter-rater secondary analysis, the vallecula and pyriform sinus kappa values were perfect (kappa = 0.959 and kappa = 0.967, respectively). In the intra-rater analysis, perfect kappa values were obtained for the vallecula and pyriform sinus in the no-training group and less-experience subgroup (kappa = 0.9918 and kappa = 1.0 for the vallecula, and kappa = 1.0 and kappa = 0.9902 for the pyriform sinus, respectively) In the inter-rater analysis, perfect kappa values were obtained for the vallecula and pyriform sinus in the no-training group and less-experience subgroup (kappa = 0.9507 and kappa = 0.9606 for the vallecula, and kappa = 0.9836 and kappa = 1.0 for the pyriform sinus, respectively). The Turkish translation of the Yale pharyngeal residue severity rating scale demonstrated high validity and reliability scores in determining pharyngeal residue location and value in the fiberoptic endoscopic evaluation of swallowing.
Keywords: Pharyngeal residue; Validity; Swallowing; Vallecula; Pyriform sinus; Therapy; Scale; ACCUMULATED OROPHARYNGEAL SECRETIONS; FIBEROPTIC ENDOSCOPIC EVALUATION; VIDEOFLUOROSCOPY; INSTRUMENTS; ADAPTATION; ASPIRATION